Reversible first-degree atrioventricular block due to hyperthyroidism - Aksüyek Savaş Çelebi; Basri Amasyalı (KARE Publishing, 2017)
Hyperthyroidism often causes tachyarrhythmia. Reversible atrioventricular block caused by hyperthyroidism is rare occurrence. Presently described is a case of atrioventricular block due to hyperthyroidism and recovery after antithyroid treatment.